Primary Antiphospholipid syndrome presenting with acute ST elevated MI with normal coronaries - Islam, Lohani Md Tajul; Chowdhury, Abdul Wadud; Rahman, AKM Fazlur; Sultana, Sarjana; Osmany, DMM F; Hasan, Md Nazmul (University Heart Journal, 2017)
Myocardial infarction (MI) under the age of 40 years accounts for around 3% of cases of coronary artery disease. Coronary artery atherosclerosis is less commonly the underlying aetiology in this age group and more comprehensive investigation of the cause is required. Antiphospholipid syndrome is a rare cause for MI which can be found younger age group. Here,We report a22 years young patients with MI who had normal coronary arteries on coronary angiogram that proved to have primary APS. University Heart Journal Vol. 12, No. 1, January 2016; 49-50